Effects of reinforcement on wear resistance of aluminum matrix composites - Pramanik, Alokesh (Nonferrous Metals Society of China, 2016)
The effect of reinforcement on the wear mechanism of metal matrix composites (MMCs) was investigated by considering different parameters, such as sliding distance (6 km), pressure (0.14-1.1 MPa) and sliding speed (230-1480 r/min). The wear mechanisms of an MMC and the corresponding matrix material under similar experimental conditions were compared on a pin-on-disc wear machine. The pins were made of 6061 aluminum matrix alloy and 6061 aluminum matrix composite reinforced with 10% Al2O3 (volume fraciton) particles (6-18 µm). The disc was made of steel. The major findings are as follows: the MMC shows much higher wear resistance than the corresponding matrix material; unlike that of matrix material, the wear of MMC is very much linear and possible to predict easily; the wear mechanism is similar for both materials other than the three-body abrasion in the case of MMC; the reinforced particles resist the abrasion and restrict the deformation of MMCs which causes high resistance to wear. These results reveal the roles of the reinforcement particles on the wear resistance of MMCs and provide a useful guide for a better control of their wear. © 2016 The Nonferrous Metals Society of China.